Methane production and in vitro digestibility of low quality forages treated with a protease or a cellulase - Cantet, Juan Manuel (2015)
The objective was to assess the impact of application of two enzyme mixtures on the in vitro dry matter digestibility, neutral detergent fibre digestibility, net cumulative gas production and methane production after 24 h of incubation of Milium coloratum (formely Panicum coloratum) and a Patagonian meadow grassland. A protease (Protex 6-L) and a fibrolytic enzyme (Rovabio) were assessed at three application rates (30, 60 and 90 mg/100 mL of distiller water) on the substrates. Meadow samples were higher toMilium ones (P < 0.05) forin vitro dry matter digestibility and net cumulative gas production at 24 h. Nevertheless, Milium was ~11% higher than meadow (P < 0.05) for methane when expressed as a proportion of digested dry matter (g/kg). Rovabio did not induce differences in any variable, but the addition of Protex reduced (P < 0.05) in vitro dry matter digestibility in both substrates without bringing about differences in methane production. Collectively, the addition of these enzymes did not benefit in vitro ruminal fermentation of low quality forages.